Multi-electron donation promotes the photocatalytic conversion of carbon dioxide to methane in a covalent bonded metal-complex/quantum dots hybrid catalyst - Zhao, Qian; Abdellah, Mohamed; Liu, Yang; Meng, Jie; Zou, Xianshao; Enemark-Rasmussen, Kasper; Zhou, Yu; Li, Yi; Cao, Yuehan; Chen, Yijiang; Eliasson, Nora; Zhou, Ying; et al. (Chemical Engineering Journal, 2025)
Multi-electron donation remains a challenge for CO2 photocatalytic conversion to multi-electron products due to the efficient Auger recombination or annihilation at multiple excitation conditions for conventional molecules or semiconductor photocatalysts. In this paper, we demonstrated possible multi-electron donation within a quantum dot (QD)/metal complex hybrid photocatalyst system when multiple metal complexes are attached to one QD. Structural characterization first confirmed the number of [Re(4,4′-R-bpy)(CO)3Br] catalysts (bpy = 2,2′-bipyridine) attached per QD. The time-dependent density functional theory (TD-DFT) calculation identified that photoexcited electrons directly reside on the ligand of the metal complexes. Combining the studies from transient visible and infrared spectroscopies, we reveal that the efficient multi-electron transfer from one excited QD can be achieved when two metal complexes are anchored to one QDs with an electron injection time shorter than one ps. The transferred electrons are localized at the Re-complex while the holes are delocalized in the QD with a long lifetime. This can guarantee efficient multi-electron donation during photocatalytic reactions. Consequently, such multiple catalysts attachment facilitates the CO2 photocatalytic reduction, where unconventional methane production involving the donation of eight electrons has been significantly enhanced with an enhanced CH4 evolution rate of 130 μmol/g/h and apparently quantum yield of 1.7 % in acetonitrile medium with triethanolamine as sacrificial electron donor. This work establishes a strategy to control CO2 reduction products via tuning the multi-electron donation pathways through molecular engineering.
Keywords: CO photocatalytic reduction; Hybrid catalyst; Methane; Multi-electron donation; Quantum dot